Effective velocity of biomass particles in a fluidized bed reactor - Soriano Sánchez, Irene (My University, 2019)
The growing greenhouse gas emissions (GHG) in the EU are produced mainly by the consumption of energy. For this reason, using more sustainable energy systems will contribute to reduce these emissions and then help to mitigate the climate change and the air pollution. The CFB (circulating fluidized bed) technology has the capability of burning a wide range of fuels meeting SOx and NOx limits, which makes it an attractive energy system to achieve a successful efficiency of the combustion. However, to ensure an efficient conversion, it is necessary to achieve an effective mixing of the bed material and the fuel particles (controlled in axial and lateral directions). This control is not easy due to the chaotic behavior of the solid particles inside the furnace. The present work investigates the behavior of the mixing of biomass particles (wood chips and wood pellets) when they circulate in a CFB when there is interaction with the inert particles and when there is not. For doing this investigation, the terminal velocities of each kind of biomass that were taken in the laboratory and the current existing models (by MATLAB) were compared.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering